2017
DOI: 10.4103/njms.njms_82_14
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal schwannoma

Abstract: Schwannoma is a benign tumor of the nerve sheath arising from the perineural schwann cells. The nerves most commonly involved in schwannomas of the head and neck are the vagus and the cervical sympathetic chain. Trigeminal schwannomas are rare tumours. A 17 year old male patient with a chief complaint of swelling on face was diagnosed as suffering from bening tumor extending from cranial base (from foramen ovale) to the parapharengeal space. Mandibular access osteotomy was done to expose the tumor. Surgical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…These lesions are isointense to slightly hyperintense on T1-weighted images and isointense to hypointense on T2-weighted images. 15 A recently reported study revealed that due to the presence of melanin granules, MS and metastatic schwannomas have a similar appearance on MRI. A dumbbell-shaped growth and cystic structure are the indirect signs that favor MS over metastatic schwannomas.…”
Section: Discussionmentioning
confidence: 97%
“…These lesions are isointense to slightly hyperintense on T1-weighted images and isointense to hypointense on T2-weighted images. 15 A recently reported study revealed that due to the presence of melanin granules, MS and metastatic schwannomas have a similar appearance on MRI. A dumbbell-shaped growth and cystic structure are the indirect signs that favor MS over metastatic schwannomas.…”
Section: Discussionmentioning
confidence: 97%
“…TSs are benign tumors with slow growth that can develop anywhere in the intracranial and extracranial regions due to the course of the trigeminal nerve [19] . The course of the trigeminal nerve mainly involves 4 anatomical regions, including the trigeminal root in the PCF (subdural space), the trigeminal root or gasserian ganglion (GG) in the area of Meckel's capsule (interdural space), the trigeminal branches of the interdural structures, and the extracranial peripheral branches of the trigeminal nerve (epidural space) [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal schwannomas are rare tumors, accounting for 1-2% of all intracranial schwannomas and tend to occur predominantly in the 4th-6th decades [1]. The lesions are solitary, slow growing, and generally not associated with neurologic symptoms [2]. The standard treatment is surgery, and these tumors were said to be radioresistant [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The lesions are solitary, slow growing, and generally not associated with neurologic symptoms [2]. The standard treatment is surgery, and these tumors were said to be radioresistant [2,3]. However, Kharod et al reported recently that fractionated radiation therapy for benign nonacoustic schwannoma to a total dose of 50 Gy provided excellent local control and minimal morbidity [4].…”
Section: Discussionmentioning
confidence: 99%